2008
DOI: 10.1002/jso.21133
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence in patients following curative resection of early gastric carcinoma

Abstract: Early gastric cancer patients, who were elderly, had lymphatic and submucosal involvement, and patients with a positive family history of cancer, tended to have a greater risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 21 publications
4
28
1
3
Order By: Relevance
“…Early tumor recurrence has been associated with lymph node metastasis and a poor prognosis [7,16,17]. In our study we observed that tumor recurrence and prognosis of T1a (tumor invades mucosa) cancer were similar to those for T1b (tumor invades submucosa) cancer (p [ 0.05), and we identified lymph node metastasis as an independent risk factor for tumor recurrence, as well as an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Early tumor recurrence has been associated with lymph node metastasis and a poor prognosis [7,16,17]. In our study we observed that tumor recurrence and prognosis of T1a (tumor invades mucosa) cancer were similar to those for T1b (tumor invades submucosa) cancer (p [ 0.05), and we identified lymph node metastasis as an independent risk factor for tumor recurrence, as well as an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 67%
“…The survival rate of patients with EGC exceeds 90 % in Japan [3,4] and in Western countries [5]. Variable rates of recurrence of EGC have been reported in these countries, ranging from 2.1 to 12.4 % [6][7][8]. The seventh edition of the American Joint Committee on Cancer (AJCC) staging system was published in 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Age, lymphatic metastasis and submucosal invasion have been reported to be significantly associated with recurrence of gastric cancer [25] . In the current study, only 5% (4/80) of patients with early gastric cancer experienced early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…49 Macroscopic PC could be reduced by the use of neoadjuvant chemotherapy (NACT). 23,45 A paper published by Yano and colleagues reported a complete remission of peritoneal metastasis in 4 over 26 patients (15.4%) with PC from GC after NACT. 50 Inokuchi and colleagues showed partial response in 9 of 13 patients (69%) following NACT for PC from GC.…”
Section: Treatment and Prevention Of Peritoneal Carcinosismentioning
confidence: 99%
“…21,22 Many studies showed that polymerase chain reaction using CEA, CEA/CK20 target genes provides a greater sensitivity than peritoneal citology in detecting free cancer cells and it will assist in reducing understimated advanced GC cases allowing a better patients selection and resulting appropriate treatment combinations. 23 analysis by Kai-Deng and colleagues, 27 demonstrated the prognostic value of molecular analysis of peritoneal fluid in GC patients also in cases with negative exfoliative cytology in terms of overall survival, disease free survival and peritoneal recurrence free-survival in GC patients receiving curative treatment. Literature data clearly demonstrated the necessity to prosecute on the way to prevent the PC in AGC by increasing the power of patient selection instruments and by anticipating PC with all the necessary and effective methods, especially by administering intraperitoneal chemotherapy in all those patients at high risk for PC.…”
Section: Introductionmentioning
confidence: 99%